Chaining in interpreted interaction : Finnish Sign Language interpreting in an English-medium educational setting - Alapuranen, Marjo-Leea (2016)
Interaction is always multimodal. Multimodality means that meanings are conveyed by using different semiotic resources, such as language, gestures, facial expressions, written text and pictures. Even though it is considered that also interpreted interaction is multimodal, this aspect of the interpreters’ work is often neglected in research and focus on how interpreters utilize multimodality in their work is called for.